Housing Solutions: Found Architecture, the Vernacular, and the Bungalow for Washington’s Teachers’ Homes - Felber, Lynette (My University, 2011)
“Housing Solutions: Found Architecture, the Vernacular, and the Bungalow for Washington’s Teachers’ Homes” was a challenging project because it researched a debate about school architecture that circulated primarily between 1915 and 1916. Publications dating back to this period are nearly archival, and as a distance education student I needed many resources that were only available to me through interlibrary loan. The Goucher Library staff, particularly Distance Learning Librarian Yvonne Lev and Research Services Librarian Randy Smith, was instrumental in helping me access rare materials. The idea for this paper began with my discovery of Josephine Corliss Preston, Washington Superintendent of Public Schools (1913-28). Preston was a national leader in promoting teacher cottages, or “teacherages,” to house rural teachers. I began my search on the Internet and found that Preston’s original 1915 pamphlet, Teachers’ Cottages In Washington, was available through Google Books. This publication offered a valuable primary source, including photographs and plans for the cottages. The pamphlet led me to search the databases of the library. As I discovered more articles published on the subject circa 1915-16, I also used their bibliographies to add further sources to my list -- some of the publications were too obscure to be included in databases. Ultimately, my working bibliography included sources ranging from popular culture (Ladies’ Home Journal) to journals for educators, such as the American School Board Journal. The latter was only available on microfilm, but the staff procured an extended loan so that I could read several years of the issues on the microfilm reader at my public library. The research process is cumulative and collaborative: each source leads to another source, each inquiry to further development. The final bibliography for my paper contained thirty-eight highly relevant sources retrieved with the aid of the Goucher Library staff and collections.
Julia Rogers Research Prize: Graduate Winner, 2011